Relevansi Perkembangan Ilmu di Barat dan Jenis-Jenis Komunikasi Penalarannya dalam Praktik Pendidikan Islam - Ahmad Wahyu Hidayat; Sigit Tri Utomo (Institut Islam Nahdlatul Ulama Temanggung, 2020)
The data collection method in this research uses literature study. In this stage, the researcher tries to select data (books) that have relevance to the history of the development of science in the west with the types of communication of the reasoning (deductive, inductive, and abductive). In this paper the analysis used with hermeneutics, the authors explain behind the text there is context meaning or behind the explicit meaning there is an explicit meaning if interpreted literally can be interpreted as an interpretation or interpretation. This method step is intended to capture the meaning, value and historical purpose of the development of science in the west with the types of communication of the reasoning (deductive, inductive, and abductive). Then the writer also uses synthesis analysis which means the stages of an object of scientific study that connects an articulation of meaning to one another and then a knowledge with new articulation in the form of the historical urgency of the development of science in the west with the types of communication of reasoning (deductive, inductive, and abductive). The author also uses content analysis, namely research conducted on information documented in recordings, both images, sounds, writing and others. With this method data analysis and processing will be carried out scientifically about the contents of the written history of the development of science in the west with the types of communication of the reasoning (deductive, inductive, and abductive). The results showed that knowledge developed since ancient times, humans are still influenced by myths and mystics, knowledge is increasingly developing and becoming a science, which erodes the understanding of myths and mysticism. In other words, science can logic a knowledge; Science began to develop in ancient Greece which began by Socrates along with the birth and development of philosophy in the 6th century BC, the golden age of science began Aristotle continued by his student, Plato. Deductive reasoning usually departs from a syllogism of statements, general arguments then with a logical mindset / analysis that analyzes it into a statement as a special form, while inductive reasoning is a form of conclusions drawn from an argument, specific statements then with logical reasoning generalized to a general conclusion and abductive reasoning shows a conclusion of an argument / theory whose truth is clear from an observation / research that has been done, purely based on the most reasonable reasoning.